Peru : Financial Sector Assessment Program-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report, 2018)
The overall quality of Peru's supervisory approach and regulation of the banking sector is strong. Some areas for enhancement remain. A key area that needs strengthening relates to the powers and regulatory framework for consolidated and cross-border supervision. The FSAP undertook a full graded Basel Core Principles (BCP) assessment of the essential criteria. The 2011 BCP update assessment found that bank regulation and supervision was of high quality and no principles were scored non-compliant or materially non-compliant. The current assessment shows that the SBS has maintained and further enhanced its regulatory and supervisory framework.